2007
DOI: 10.1681/asn.2006121402
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Role of Reactive Nitrogen Species in Polymicrobial Sepsis-Induced Renal Peritubular Capillary Dysfunction and Tubular Injury

Abstract: Acute kidney injury (AKI) remains a frequent and serious complication of human sepsis that contributes significantly to mortality. For better understanding of the development of AKI during sepsis, the cecal ligation and puncture (CLP) murine model of sepsis was studied using intravital video microscopy (IVVM) of the kidney. IVVM with FITC-dextran was used to determine the percentage of capillaries with continuous, intermittent or no flow at 0 (sham), 10, 16, and 22 h after CLP. There was a dramatic fall in cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
136
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(146 citation statements)
references
References 44 publications
5
136
1
4
Order By: Relevance
“…21,26 Similarly, rodent models of acute endotoxemia suggest that cortical peritubular capillaries are among the first renal structures injured. [27][28][29][30] Interestingly, despite an apparent full recovery of renal function at 48 hours, functional capillary density recovered only partially. 27 Moreover, areas of compromised cortical microvascular perfusion have been shown to correlate with renal tubular cell stress in corresponding regions, suggesting important links between altered peritubular microcirculation and epithelial cell dysfunction.…”
Section: Peritubular Microcirculation In Akimentioning
confidence: 98%
See 3 more Smart Citations
“…21,26 Similarly, rodent models of acute endotoxemia suggest that cortical peritubular capillaries are among the first renal structures injured. [27][28][29][30] Interestingly, despite an apparent full recovery of renal function at 48 hours, functional capillary density recovered only partially. 27 Moreover, areas of compromised cortical microvascular perfusion have been shown to correlate with renal tubular cell stress in corresponding regions, suggesting important links between altered peritubular microcirculation and epithelial cell dysfunction.…”
Section: Peritubular Microcirculation In Akimentioning
confidence: 98%
“…[27][28][29][30] Interestingly, despite an apparent full recovery of renal function at 48 hours, functional capillary density recovered only partially. 27 Moreover, areas of compromised cortical microvascular perfusion have been shown to correlate with renal tubular cell stress in corresponding regions, suggesting important links between altered peritubular microcirculation and epithelial cell dysfunction. 27 These findings were corroborated by a study by Gupta et al, 31 in which quantitative two-photon intravital microscopy revealed markedly reduced peritubular capillary blood flow in an endotoxemia model in rats.…”
Section: Peritubular Microcirculation In Akimentioning
confidence: 98%
See 2 more Smart Citations
“…Molitoris (16) illustrated the phases of ischemic acute renal failure, dividing them into initiation, extension, maintenance, and recovery, and indeed this paradigm can be extended to overlap with processes in septic AKI. For instance, Wu et al (14) identified early severe reduction of peritubular capillary perfusion leading to tubular injury in a rodent cecal ligation and perforation model of sepsis using intravital videomicroscopy, but ongoing endothelial dysfunction, with loss of regulation of vascular tone, perfusion, permeability, inflammation, and adhesion, would lead to extension of this injury as proposed by Molitoris and Sutton (17) in their work on ischemic acute renal injury.…”
Section: Pathophysiology and Classification Of Sepsis-induced Akimentioning
confidence: 99%